2019
DOI: 10.7567/1347-4065/ab124f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of growth parameters for ScAlN-barrier HEMT structures by plasma-assisted MBE

Abstract: Due to its outstanding polarization properties and the possibility of lattice-matched growth on GaN, Sc x Al 1-x N is a promising material among group III nitrides providing a wide field of potential applications in modern semiconductor technology. However, epitaxial growth of Sc x Al 1-x N by MBE is still in an early stage of research. In this work, Sc x Al 1-x N samples were grown by plasma-assisted MBE on GaN-on-sapphire templates under a variety of growth conditions and pulsed supply of Sc and Al, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 35 publications
0
26
1
Order By: Relevance
“…The N* content at 200 W plasma power was calculated from X‐ray diffraction analysis of the Al content and thickness of Al x Ga 1− x N‐GaN layers (not shown) grown at 200 W. The total nitrogen flux also contains N 2 molecules that do not contribute to crystal growth because aluminum does not react with diatomic nitrogen under these temperature and pressure conditions. Nitrogen‐rich growth conditions were utilized to promote smooth surfaces and unwanted metallic inclusions, as has been demonstrated in the literature . As aluminum has thermodynamic preference to bond to nitrogen over scandium, excess scandium would be expected to remain on the surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N* content at 200 W plasma power was calculated from X‐ray diffraction analysis of the Al content and thickness of Al x Ga 1− x N‐GaN layers (not shown) grown at 200 W. The total nitrogen flux also contains N 2 molecules that do not contribute to crystal growth because aluminum does not react with diatomic nitrogen under these temperature and pressure conditions. Nitrogen‐rich growth conditions were utilized to promote smooth surfaces and unwanted metallic inclusions, as has been demonstrated in the literature . As aluminum has thermodynamic preference to bond to nitrogen over scandium, excess scandium would be expected to remain on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…These attractive properties have allowed Sc‐III nitrides to find use in applications such as bulk acoustic wave (BAW) resonators and microelectromechanical systems (MEMS) . Magnetron sputtering has been utilized to deposit thin film Sc x Al 1− x N, and more recently, molecular beam epitaxy (MBE) to grow Sc‐III nitrides films . However, few reports provide information of the oxygen content in the scandium‐containing films.…”
Section: Introductionmentioning
confidence: 99%
“…By theoretical calculations, it has been found that ScAlN has high spontaneous polarization. , This finding expands the applications of ScAlN, because the high polarization of ScAlN allows it to provide high polarization-induced electron sheet charge at the heterostructure interface. As a result, ScAlN has been proposed as a barrier layer in GaN-based high-electron-mobility transistors (HEMTs). One of the characteristics of ScAlN is that the spontaneous polarization greatly varies depending on the Sc concentration . Furuta et al found that the large change in the metal–nitrogen bond length along the c -axis of the wurtzite structure with increasing Sc concentration results in a large increase in the spontaneous polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxial integration of wurtzite ScAlN on GaN was demonstrated recently with molecular beam epitaxy (MBE) and metal–organic chemical vapor deposition, , indicating the ability to produce a higher quality thin film material when compared with traditional sputtering techniques. One key area to exploit the high inherent polarization of ScAlN is in the design of next-generation III–N HEMTs, where ScAlN has been used as a barrier layer to increase channel charge densities by a factor of 5 higher than AlGaN-barrier GaN HEMTs. ,, …”
Section: Introductionmentioning
confidence: 99%
“…One key area to exploit the high inherent polarization of ScAlN is in the design of next-generation III−N HEMTs, where ScAlN has been used as a barrier layer to increase channel charge densities by a factor of 5 higher than AlGaNbarrier GaN HEMTs. 9,11,17 Although the growth and characterization of ScAlN films is growing in popularity in the research community, there is still much to be elucidated about its electrical properties especially its band alignments with GaN. It has long been known that valence and conduction band discontinuities influence the behavior of electronic devices.…”
Section: Introductionmentioning
confidence: 99%